TINJAUAN KEBUGARAN JASMANI DAN MOTIVASI MURID KELAS TINGGI SEKOLAH DASAR - Ezza Charolin, Viona; Hardiansyah, Sefri; Sepriadi; Apriyano, Berto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the suboptimal implementation of Physical Education, Sports, and Health (PJOK) learning at Muhammadiyah Pasar Manna Elementary School in South Bengkulu, as indicated by low student learning outcomes and signs of issues related to physical fitness and learning motivation. Therefore, this study aims to determine the level of physical fitness and learning motivation among upper-grade students at the school. This research employed a quantitative descriptive method with a population consisting of all fourth and fifth-grade students, totaling 27 individuals. The instruments used were the Indonesian Student Fitness Test (TKSI) for phase C, which includes the child ball test, tok tok ball test, move the ball test, shuttle run 4x10 meters, and 600-meter run, as well as a learning motivation questionnaire using a Likert scale. The results showed that the students' physical fitness level fell into the poor category with an average score of 12.63, while their motivation level was in the good category with an average score of 152.78. These findings indicate that low physical fitness serves as the main inhibiting factor in PJOK learning, despite the students' motivation being relatively good. In conclusion, efforts are needed to improve physical fitness through the optimization of PJOK instruction and better management of physical activities at school.